Work-life harmony for creative minds in the advertising industry. - Chan, Cheryl Yu Pei. (2011)
Creative individuals (i.e., copywriters and art directors) face many challenges, some unique to the advertising industry, in their attempt to meet the competing demands of their work and personal commitments. Our study examines the various work-life conflicts that creative individuals in Singapore face, the factors that contribute to these conflicts, and the effects work-life harmony has on creativity. In-depth interviews with four human resource personnel and eight creative individuals were conducted, and the websites of 17 advertising agencies were content-analysed. The Grounded Theory approach was employed for the data analysis of the study as it allows for a holistic exploration and flexibility for new emergent themes. Findings reveal two key factors preventing creative individuals from attaining work-life harmony – the inability of creative individuals to separate work from their personal life, and unpredictable factors related the nature of the advertising industry. There is a need for agencies to place greater importance on helping employees achieve work-life harmony (i.e., introduce official work-life policies, flexible work places) as it is a key factor in employee retention and the idea generation process of creative individuals.